Prediction of Employment Status Choice Intentions - Kolvereid, Lars (Entrepreneurship Theory and Practice, 1996)
The present research applied the theory of planned behavior to predict employment status choice, defined as the intention to enter an occupation as a wage or salaried individual or as a self-employed one. The role of family background, sex, and prior self-employment experience was also investigated. Using a sample of 128 Norwegian undergraduate business students, the findings strongly support the theory of planned behavior as applied to employment status choice intentions. Moreover, demographic characteristics were found to influence employment status choice intentions only indirectly through their effect on attitude, subjective norm, and perceived behavioral control.